CHALLENGES OF DEVELOPMENT OF THEORETICAL BASES IN INTERCULTURAL COMMUNICATION AS THE FIRST FACTOR OF TEACHING FOREIGN ANGUAGES - Y. X. Kushakov (Bright Mind Publishing, 2025)
In this article, the main problems of the theoretical bases of development of intercultural communication as an important factor in teaching a foreign languages are revealed. The author highlights the key tendencies and problems in this sphere.
Keywords: Culture, intercultural, communication, various approaches, authentic, task, demand, function, functional.